Solomon Islands : Tax Summary and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2007)
This paper presents the Tax Summary for the Solomon Islands. The paper discusses that normal business expenses are deductible against chargeable income. A USD 7,800 personal exemption applies to both resident and nonresident individuals. This general exemption is subject to apportionment on a pro-rata basis should the individual commence work part way through the year. In addition, the first USD 5,000 of interest income on deposits made with any savings bank or on fixed deposit accounts with any bank in the Solomon Islands are excluded from chargeable income.